Acute Pancreatitis Secondary to Diabetic Ketoacidosis Induced Hypertriglyceridemia in a Young Adult with Undiagnosed Type 2 Diabetes - Singla, Animesh A; Ting, Francis; Singla, Apresh (JOP. Journal of the Pancreas, 2015)
Context The triad of acute pancreatitis, hypertriglyceridemia and diabetes is a rare occurrence. Case report A previously well 19-year-old male presented to the emergency department with 24-hour history of epigastric pain, associated with polyuria and nausea. Biochemical markers showed the presence of hyperglycemia (blood sugar level 15 mmol/L) and ketonemia (5.3 mmol/L). Further investigation revealed severe hypertriglyceridemia (4,009 mg/dL) and elevated lipase (1,714 U/L). Abdominal ultrasound confirmed the diagnosis of acute pancreatitis. He was transferred to intensive care, where he received i.v. hydration, insulin and dextrose infusion. His metabolic derangements gradually resolved. His glycosylated hemoglobin was 13%, indicating the presence of chronically elevated blood sugars. Conclusion The possible pathophysiology and management of this unusual triad: diabetic ketoacidosis, hypertriglyceridemia and acute pancreatitis, are explored in this paper. Image: Edematous pancreas and adjacent fluid collection.